COASTAL MORPHODYNAMIC STUDY USING MULTI TEMPORAL DATA IN BANTEN BAY, INDONESIA - Kesumajaya, I Nyoman S; Sutikno, Sutikno; Poniman, Aris; Wijanarto, Antonius (Badan Informasi Geospasial in Partnership with MAPIN, 2009)
Banten Bay and its surrounding area has been indicated as the coastal areas that serious the environmental problems due to poor management of the natural marine resources that has been going for a long time. This study was carried out focusing on the coastal morphodynamic processes, using the multi temporal satellite images as the main sources of the information. The topographic data of year 1923 has been used for the baseline data for research carried out supported by others thematic data that can be collected for the area of study. The multi temporal images used were aerial photographs at 1:30.000 scale acquired in 1981/1982 and at 1:50.000 scale acquired in 1994; SPOT XS images dated 1990 and 1997 as well as LANDSAT MSS of 1976; LANDSAT TM of 1996 & 2000. Geomorphological map for the study area has been prepared on 1:50,000 scale and the coastal morphodynamic were studied in detail using remote sensing approach completed with the ground-truthing using stratified random sampling techniques. Physical aspect related to coastal changes can be treated throughout vector data gatherred from topographic and the thematic data. The results indicate that there were coastal changes has been found in some where Eastern part of the coast line segment close to Pulau Dua (Dua Islands) as tombolo formation. To the east, Ciujung Delta has been growing with typical bird foot delta. On the other hand, abrasion process took place in Tanjung Pontang (old Ciujung Delta) and also within the coast line segment at Lontar Village. The rate of abration processes within the study area has been 0,0436 mm/yr for the coral islands distributed within shallow coastal sea in the study area, 0,0316 mm/yr along the adesitic volcanic coast line at the western part of the study area, and 0,503mm/yr in soft sediment rock area. Deposition processes were also active in the coastal area between Bojonegoro up to Kamanjungan that is indicated by the bathymetry changes from 2.5 m in the year 1923 to < 1.25 m at present condition in the Karanghantu harbor at a distance of 100 m from the present coast line.Keywords: morphology, dynamics, coastal zone, remote sensing, coastline change.